Experimental research of single-piece separation process in magazine loader of shoe machines - Поповіченко, Сергій Анатолійович; Орловський, Броніслав Вікентійович (Eastern-European Journal of Enterprise Technologies, 2015)
The paper describes the method and design of the experimental setup for investigating the single-piece separation process in magazine loader of shoe machines, in which an additional mechanism for vertical shock impact on the stack of parts in the initial moment of single-piece separation is used to improve the single-piece separation conditions. The influence of factors such as single-piece separation force, vertical shock pulse and the number of parts in the stack on the single-piece separation process was examined. It was found that using the shock pulse allows to reduce the single-piece separation force by 30-40% compared to its value in the separation of parts from the stack without the shock pulse. It can be concluded about the feasibility of using the shock impact on the stack of parts in magazine loader of shoe machines to reduce the single-piece separation force and thus improve the separation process conditions.